Optimalisasi Inovasi dalam Ibadah Minggu sebagai Upaya Meningkatkan Partisipasi Jemaat dalam Pelayanan di GKSI Bukit Sion Bongkok - Jefri Feoh; Riste Tioma Silaen (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study aims to explore and analyze the optimization of innovations in Sunday worship as a strategy to enhance congregational participation in ministry at GKSI Bukit Sion Bongkok. The research background is based on the low level of active involvement among congregants, despite the church having sufficient human resources potential. This study employs a qualitative descriptive method with a case study approach, involving in-depth interviews with pastors, congregants, and ministry teams, participatory observation during Sunday worship, and analysis of church documents related to ministry programs. The results indicate that implementing worship innovations, such as creative and contextual liturgy development, utilization of audio-visual technology, and participatory approaches in praise, prayer, and sermons, significantly enhances the emotional and spiritual engagement of congregants. Congregants become more motivated to actively participate in various ministry activities, both within and outside the church. Nevertheless, challenges were identified, including resistance from some congregants to change, budget limitations, and the need for continuous ministry team training. Based on these findings, it is recommended that the church implement sustainable strategies, including regular evaluation of worship innovations, training for ministry teams, and adaptation of innovations to cultural and congregational needs. This study provides practical contributions to church ministry development by emphasizing the importance of innovation as a means to strengthen congregational participation and foster an active spiritual community. The findings may also serve as a reference for other churches in designing Sunday worship that is responsive, creative, and capable of encouraging active congregational involvement in ministry.